Subjective Symptoms in Magnetic Resonance Imaging Personnel: A Multi-Center Study in Italy - Bravo, Giulia; Modenese, Alberto; Arcangeli, Giulio; Bertoldi, Chiara; Camisa, Vincenzo; Corona, Gianluca; Giglioli, Senio; Ligabue, Guido; Moccaldi, Roberto; Mucci, Nicola; Muscatello, Martina; Venturelli, Irene; et al. (Frontiers in Public Health, 2021)
Introduction: Magnetic Resonance Imaging (MRI) operators have a relevant exposure to static and low-frequency time-varying magnetic fields. In these workers an increased prevalence of different subjective symptoms has been observed. Objective of our study was to investigate the prevalence of non-specific subjective symptoms and of "core symptoms" in a group of MRI operators working in different centers in Italy, and of possible relations with occupational EMF exposure and other personal and occupational characteristics. Methods: The occurrence of 11 subjective symptoms was evaluated with a specific questionnaire in 240 subjects working in 6 different Italian hospitals and research centers, 177 MRI health care and research operators and 63 unexposed subjects employed in the same departments. Exposure was estimated according to the type of MRI scanner (≤1.5 T vs. ≥3 T), and to the number of MRI procedures followed. The possible associations among symptoms and estimated EMFs exposure, the main characteristics of the population and job stress perception were tested. Results: The 86 % of the operators reported at least one symptom; drowsiness, headache and sleep disorders were the most frequent. The total number of symptoms did not differ between exposed and controls. A positive relation was found between the total number of procedures and the total number of weekly symptoms. The number of core symptoms was related to the total number of MRI procedures performed in one year (p = 0.07). Subjects with high level of perceived stress complained more symptoms (p = 0.0002). Conclusions: Our study did not highlight an evident association between the occurrence of subjective reversible symptoms, including the more specific “core symptoms”, and the occupational exposure of MRI operators to static and low-frequency time-varying magnetic fields.. On the other hand, a role played by work stress seems not negligible. In further research in this field, measurements of EMF exposure should be considered. In any case, the collection of symptoms appearance seems a useful tool for the health surveillance of MRI operators. Nevertheless, due to the subjective nature of these symptoms, the possible role of occupational stress should also be considered in the evaluation of the results.